STAFFING ISSUES IN THE RUSSIAN MEDICINE - Svirin, Yury Alexandrovich; Anatolievich Mokhov, Alexandr; Aleksandrovich Gureev, Vladimir; Nikolaevna Volkova, Olga; Evgenyevna Titor, Svetlana (Revista Inclusiones, 2021)
The article examines the staffing issue in healthcare during the transition to an innovative path of growth. The following proposals on solving the personnel shortage issue in the medical industry have been analyzed: the increase in the number of students, development of the targeted training for specialists in the industry, and the increase in its scope; and the introduction of a mechanism for the “distribution” of graduates prepared at the expense of the federal budget. A critical analysis of the existing proposals is carried out from the standpoint of the challenges facing innovative medicine. Based on the study conducted, a conclusion is drawn about the need for a significant modernization of the healthcare model or its replacement with another model based on the urgent need to solve the staffing issue in the industry. Methods: In the course of the study, the following methods have been used: system analysis, comparative analysis of the Russian and foreign practice, theoretical methods (analysis, synthesis, concretization, generalization); statistical methods (comparison using statistical data), empirical methods (study of the experience of educational medical organizations, normative literature; pedagogical observation), as well as general scientific methods of cognition. The goal of this study is to identify ways out of the systemic personnel crisis in the healthcare sector in the Russian Federation. Results of the study: The results and conclusions made within the framework of this article allow stating that the main reasons for the growing personnel shortage in the domestic healthcare include the following: a clear discrepancy between the income level and current needs as well as the complexity and responsibility in the work of a doctor; high duration of preparation for the profession, therefore, more significant direct and indirect costs of an individual or its family for training; consolidation of the “conflict model” of healthcare; devaluation of the social status of the doctor; legalization of medical care; and social and legal vulnerability of the medical worker. The socio-economic system in the system of measures to resolve the staffing issue is leading (the salary of a physician, motives and incentives, guarantees, benefits, and more aspects arise from it). Practical relevance: Materials of the article can be used to develop a government policy in the field of resolving the personnel shortage in the medical field.